Trends of school effects on student achievement: evidence from NLS:72, HSB:82, and NELS:92 - Spyros Konstantopoulos (Institute for the Study of Labor (IZA), 2005)
The impact of schools on student achievement has been of great interest for the last four decades. This study examines trends of school effects on student achievement employing three national probability samples of high school seniors: NLS:72, HSB:82, and NELS:92. Hierarchical linear models are used to investigate school effects. The findings reveal that the substantial proportion of the variation in student achievement lies within schools not between schools. There is also considerable between school variation in achievement, which becomes larger over time. Schools are more diverse and more segregated in the 1990s than in the 1970s. In addition, school characteristics such as school region, school SES, and certain characteristics of the student body of the school, such as students' daily attendance, students in college preparatory classes, and high school graduates enrolled in colleges are important predictors of average student achievement. The school predictors explained consistently more than 50% of the variation in average student achievement across surveys. We also find considerable teacher heterogeneity in achievement within schools, which suggests important teacher effects on student achievement. Teacher heterogeneity in student achievement was larger than school heterogeneity, which may indicate that teacher effects have a relatively larger impact on mathematics and science student achievement than school effects.
Keywords: I2; 330; school effects; trends; student achievement